Correlation of Arm Muscle Power and Flexibility with Shot Put Ability - Jud, Jud; Rusli, Muhammad; Suhartiwi; sariul; Marsuna (Universitas Negeri Padang, 2024)
This research is a type of quantitative research with a correlational design. The population in this study was all students at SMP Negeri 10 Kendari, totaling 288 people. Based on considerations, the selected population was all male students, totaling 110 people. The sample used in this research was 33 people. Or 30% of the population, namely all existing sons. The sampling technique was carried out using a stratified random sampling technique. The instrument for measuring arm muscle power uses the two-hand medicine ball put test. Measuring the flexibility of the backbone using a sit and reach test and the flexibility of the backbone using an extension dynamometer. The test to measure bullet-rejecting ability is to perform a repulsion starting from the boundary line to where the bullet falls, which is measured in meters. The data analysis technique uses descriptive tests, analysis prerequisite tests, namely normality and linearity tests, as well as hypothesis testing with the help of SPSS 20. The magnitude of the contribution of arm muscle power and flexibility of together to shot put ability is shown by the coefficient of determination r2 x 100% = (0.946)2 x 100% = 89.50%. This can be interpreted as 89.50% of the contribution or variable contribution of arm muscle power and flexibility of the spear to shot put ability.